The Dark Side of The Moon: Unmasking Behavioral Risk Behind Fintech Adoption Among Digital Natives - Yahya, Syarief Dienan; Yahya, Andi Fauziah; Afrizal, Yogi Hady (Organizations and Markets in Emerging Economies, 2025)
The rapid expansion of financial technology ( fintech) has reshaped financial behavior, especially among digital natives in Indonesia. This study examines the impact of financial inclusion and financial literacy on online loan decisions and impulsive buying behavior, with online loan decisions serving as a mediator. A survey was conducted with 334 respondents, focusing on digital natives who have used online loan services. Using Structural Equation Modeling (SEM), the study found that financial inclusion positively influences online loan decisions, while financial literacy negatively impacts both online loan decisions and impulsive buying behavior. Notably, online loan decisions partially mediate the relationship between financial inclusion, financial literacy, and impulsive buying behavior. These findings highlight the complex role of fintech in promoting financial inclusion while also introducing behavioral risks. The study underscores the importance of financial literacy in mitigating impulsive financial behaviors among digital natives.
Keywords: Financial Inclusion; Financial Literacy; Impulsive Buying Behavior; online loan decisions; digital natives; fintech